Pelatihan Menggambar Karakter Manga dan Anime Sebagai Budaya Jepang Populer Pada Siswa Japanese Club Bahasa Jepang SMAN 6 Padang - Rita Arni; Ferdian Ondira Asa; Damai Yani (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2023)
This program was triggered by several problems faced by the partner, including students lack of knowledge about Japanese culture, particularly manga and anime, students lack of basic techniques for drawing manga and anime characters, and students’ low interest in the Japanese language.  Therefore, the community service team proposes training sessions on fundamental manga and anime character drawing techniques in order to enhance students' enthusiasm for Japanese language and culture, augment their understanding of Japanese art and culture, particularly manga and anime, boost their competence in drawing through step-by-step demonstrations and explanations of manga and anime drawing techniques, improve their general artistic abilities, and cultivate new interests in Japanese art and culture. The result showed an increase on community empowerment, specifically an enhancement on partner’s skills.